New thienylpyrrolyl-cyanoacetic acid derivatives: synthesis and evaluation of the optical and solvatochromic properties - Batista, R. M. F (2017)
The novel thienylpyrrolyl-cyanoacetic acid derivatives were obtained in good yields through a simple Knoevenagel condensation of the corresponding precursor aldehydes with cyanoacetic acid in acetonitrile at reflux, using piperidine as catalyst. The formyl precursors 1-2 were obtained through two different methods: (i) lithiation followed by treatment with DMF and (ii) Suzuki cross-coupling reaction. The novel push-pull systems were completely characterized by the usual spectroscopic techniques and the optical and solvatochromic properties were evaluated.